Konseling Krisis Dengan Pendekatan Konseling Realitas Untuk Menurunkan Kecemasan Anak Korban Kekerasan Seksual (Penelitian Single Subject di Pusat Pelayanan Terpadu (PPT) Provinsi Jawa Timur) (Jurnal Bimbingan dan Konseling Islam, 2015)
This study departs from the soaring number of cases of child abuse, especially on sexual violence. Cases of child sexual abuse triggers an increase in negative excess in children, as well as destructive behavior performed by the actors. Excesses of the negative can be a risk of anxiety, adjustment difficulties, socializing, feeling isolated, not accepted, lose the desire to play with peers, as well as discomfort in the peer group. The purpose of this study is to develop forms of counseling strategies with crisis counseling approach reality in an attempt to reduce anxiety in children victims of sexual violence in Pusat Pelayanan Terpadu (PPT) of East Java Province. This research is to design experiments ABA single subject design, research conducted at Pusat Pelayanan Terpadu (PPT) of East Java 2014 samples in this study were 3 children with an age range (13-18 years) who experienced sexual violence. Data was collected by questionnaire Taylor's Manifest Anxiety Scale (TMAS), observation, interview and documentation. To obtain a clear picture of the anxiety experienced by the counselee in a certain period, then the method of analysis used in this research is a visual inspection, the analysis was done by direct observation of the data that has been displayed in graphical form.The results of this study indicate that the three people counselee anxiety decreased after administration of crisis intervention counseling programs. Subjects 1, experienced a change in the level of 12%. Subject 2, 10%, and 3 subjects by 12%. Under baseline conditions 1 (A1), Treatment (B), Baseline 2 (A2), then the estimate of the data obtained and the tendency toward a trail of data that tend to (+) / improved. The study recommends the provision of guidance and counseling teachers, counselors, parents, researchers should be able to implement further strategies with crisis counseling counseling approach reality in an attempt to reduce anxiety in children victims of sexual violence.